GlóRí - the glottal research instrument - Yanushevskaya, Irena; Gobl, Christer; Ní Chasaide, Ailbhe; Kane, John; Dalton, John (My University, 2014)
This papers presents GlóRí - the glottal research instrument. GlóRí is a speech analysis interface which offers a flexibility and multiplicity of approaches to voice analysis. The system allows for fully automatic processing, for instance for analysis of large corpora. However, for more fine-grained studies, which may require precise voice source measurements, the systems facilitates manual optimisation of parameter settings. The present paper highlights the main features of the GlóRí system and provides illustrations of the usefulness of this approach.
Speech Prosody 7
Keywords: Glottal source; Voice source; Phonetic features; Voice quality